SME's cost of debt: A meta-analysis of borrower, creditor and financial statement verification attributes - Thomas Loy; Stefan Mohrmann (The Journal of Entrepreneurial Finance (JEF), 2022)
Private firm financing, given the far-reaching importance of non-publicly traded companies for global output and employment, is still a relatively underexplored area. Since the seminal work of Petersen and Rajan (1994), only a small branch of research into private firms' cost of debt has been established. We aggregate the full body of this research that has empirically investigated antecedents of private firms' cost of debt in a meta-analysis. The foremost antecedents can be categorized into either borrower, creditor or financial statement verification attributes. Our results reveal a set of 11 highly significant and robust determinants.
Keywords: G21; G32; 650; Cost of debt; Meta-analysis; Private firms; SME